Poverty, battered women, and work in U.S. public policy - Brush, Lisa Diane (New York ; Oxford : Oxford University Press, 2011)
This text presents findings from research on the intersection of poverty and men's coercive control of their wives and girlfriends. It articulates a progressive feminist human rights-based alternative to the conventional contention that policy should respond to poverty and abuse by reforming women's character through employment.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Abused women -- United States; Man-woman relationships -- United States; Welfare recipients -- Employment -- United States